Musical transmission and collective memory: A psychocultural study of Tujia folk songs - Gao, Ming; Krisada Daoruang; Arethit Posrithong (Environment and Social Psychology, 2025)
This psychocultural study explores the relationship between musical transmission and collective memory within the Tujia ethnic minority in China, focusing on the role of traditional folk songs as mnemonic vessels for cultural identity. Using a mixed-methods design across three generational cohorts, the study applies four novel analytical techniques—Multi-Generational Transmission Analysis (MGTA), Digital Cognitive Mapping, Biometric Coding, and Network Analysis—to examine how emotional engagement, symbolic coherence, and social learning contexts shape memory retention. The findings indicate a marked generational decline in cultural knowledge, especially in contextual understanding and symbolic literacy. Emotional synchrony during ritual-based transmission emerged as a strong predictor of memory retention, while institutional instruction showed limited efficacy. Furthermore, most lyrical and symbolic changes reflected cultural erosion rather than creative innovation. The study concludes that sustainable heritage preservation depends not only on documentation but on revitalizing embodied, affective, and community-rooted learning environments that support psychocultural continuity.